Viscoelastic and Adhesion Properties of New Poly(Ether-Urethane) Pressure-Sensitive Adhesives - Fuensanta, Mónica; Martín-Martínez, José Miguel (Frontiers in Mechanical Engineering, 2020)
New thermoplastic poly(ether-urethane) (TPUs) pressure sensitive adhesives (PSAs) have been synthesized with the prepolymer method by reacting methylene diisocyanate, different blends of polyether diols  poly(propyleneglycol) (PPG) and poly(tetramethylene ether glycol (PTMEG) , and 1,4-butanediol chain extender; different NCO/OH ratios have been used. The properties of the TPU PSAs depended on both the NCO/OH ratio and the PTMEG content in the blend. The addition of PTMEG polyol produced semicrystalline regions of the soft segments of the TPUs and inhibited the mobility of the polymeric chains, this leaded to improved cohesion of the TPU pressure sensitive adhesives; however, similar degrees of phase separation were obtained in all TPUs synthesized with different PTMEG contents. The increase of the PTMEG content in the polyols blend improved both the cohesion and the adhesion but decreased the tack of the TPU pressure sensitive adhesives. The optimal balance between the adhesion and cohesion properties was found in the TPU pressure sensitive adhesive synthesized with 50 wt% PPG + 50 wt% PTMEG and an NCO/OH ratio of 1.20.